2018
DOI: 10.1108/ijchm-06-2017-0355
|View full text |Cite
|
Sign up to set email alerts
|

The influence of perceived service fairness on brand trust, brand experience and brand citizenship behavior

Abstract: Purpose Service fairness has been conceptualized as a major part of the foodservice industry due to the intangibility of foodservice, which is difficult to be evaluated by customers. Considering this challenge, this study investigates the impacts of perceived service fairness dimensions in encouraging brand citizenship behaviors (i.e. brand enthusiasm and brand endorsement) along with the mediating roles of brand trust and brand experience in the foodservice industry. Design/methodology/approach Based on an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 61 publications
1
44
1
2
Order By: Relevance
“…The data analysis showed that there is a significant and positive relationship between experience marketing and perceived service fineness, the effect ratio is 63.6% (β = 0.636; t = 10.555; p < 0.001); our results are similar to Wu and Liang ( 2009), Su et al ( 2016), and M. Kim et al (2018). That is, if the company can make consumers have a satisfactory experience in sense, feel, thinking, action, and relate, it can promote consumers to feel fair in the shopping process.…”
Section: Discussionsupporting
confidence: 88%
“…The data analysis showed that there is a significant and positive relationship between experience marketing and perceived service fineness, the effect ratio is 63.6% (β = 0.636; t = 10.555; p < 0.001); our results are similar to Wu and Liang ( 2009), Su et al ( 2016), and M. Kim et al (2018). That is, if the company can make consumers have a satisfactory experience in sense, feel, thinking, action, and relate, it can promote consumers to feel fair in the shopping process.…”
Section: Discussionsupporting
confidence: 88%
“…Trust has to do with the feeling of security that users have when interacting with a brand ( Delgado-Ballester et al., 2003 ). In addition, the concept is related to the users' feeling of confidence that if a problem arises, the brand will try to provide a solution ( Kim et al., 2018 ). In the area of product consumption, which includes the consumption of sports services, trust is an element that significantly influences the relationship established between the buyer and the seller ( Kim and Walker, 2013 ), whereby trust makes the consumer-brand transaction-based orientation become a close, personal and lasting brand relationship ( Tong et al., 2018 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Sebagai konsekuensinya maka sangatlah penting untuk mengidentifikasi faktorfaktor yang dapat memengaruhi pengalaman pelanggan. Penelitian terdahulu menginvestigasi faktor-faktor yang memengaruhi pengalaman pelanggan pada beberapa sektor tertentu, seperti faktor perceived value, kualitas fungsional, kualitas layanan, keterlibatan karyawan-pelanggan, perceived risk, perceived useability pada sektor perbankan digital di UK (Mbama & Ezepue, 2018), faktor kewajaran harga, kewajaran prosedural, kecukupan hasil dan kewajaran interkasi di industri restoran di Korea Selatan (Kim, Shin, & Koo, 2018), faktor merchandise, layanan paska transaksi, komunikasi, komunikasi personal, atmosfir toko dan program loyalitas pada industri ritel di Malaysia (Mohd-Ramly & Omar, 2017) dan dimensi-dimensi kenyaman pada m-shopping di India (Mahapatra, 2017 Penelitian ini diharapkan dapat memberikan kontribusi mengenai faktor-faktor yang perlu diperhatikan pelaku usaha m-commerce untuk menciptakan pengalaman dan kepuasan pelanggannya dan juga memberikan tambahan literatur dalam hal kualitas layanan, perceived risk, pengalaman dan kepuasan pelanggan.…”
Section: Pendahuluanunclassified